PROFITABILITY OF THREE MAIZE HYBRIDS AS INFLUENCED BY VARYING PLANT DENSITY AND POTASSIUM APPLICATION - M. Ahmad alias H. A. Bukhsh; R. Ahmad; A. U. Malik; S. Hussain; M. Ishaque (Journal of Animal and Plant Sciences, 2011)
High plant density brings bareness in plants. Potassium (K) application is one of the solutions of this plant bareness. To explore profit of different maize hybrids under varying plant density levels, to minimize plant bareness by application of K, an  experiment was laid out in randomized complete block design with split plot arrangement, randomizing maize hybrids in main plots (H1= Pioneer-3012, H2= Pioneer-3062, H3= Pioneer – 30D55)  and plant density levels (P1 = 15 cm x 70 cm (95238 plants ha-1), P2 = 25 cm x 70 cm (57142 plants ha-1), and P3 = 35 cm x 70 cm (40816 plants ha-1) with K application (K0=0, K1=100, K2=150, K3=200 and K4=250 Kg ha-1) in subplots with four replications. It was observed that among all maize hybrids, Pioneer-30D55 produced maximum net income (Rs.92877.88 ha-1) at plant density level of 95238 plants ha-1 with the highest cost benefit ratio (2.78). Similarly, by K application grain production increased with the increase in K application. Pioneer-30D55 produced maximum grain yield (6.41 t ha-1) when K was applied @ 200 Kg ha-1 but when it was calculated economically it was found non profitable. The highest cost benefit ratio (2.71) was noted in control where no potassium was applied. It is therefore suggested that among all three maize hybrids, Pioneer-30D55 should be preferably grown at high plant density (95238 plants ha-1) with zero K application to achieve maximum profit. The reason was that high input cost of K did not respond grain yield in the same reciprocal fashion as desired.
Keywords: Maize hybrids; plant density; K application; plant bareness; profitability.